Beyond Defense: Multiple Functions of Benzoxazinoids in Maize Metabolism - Zhou, Shaoqun; Richter, Annett; Jander, Georg (Plant and cell physiology, 2018)
Abstract Benzoxazinoids are a class of indole-derived plant metabolites that function in defense against numerous pests and pathogens. Due to their abundance in maize (Zea mays) and other important cereal crops, benzoxazinoids have been the subject of extensive research for >50 years. Whereas benzoxazinoids can account for 1% or more of the dry weight in young seedlings constitutively, their accumulation in older plants is induced locally by pest and pathogen attack. Although the biosynthetic pathways for most maize benzoxazinoids have been identified, unanswered questions remain about the developmental and defense-induced regulation of benzoxazinoid metabolism. Recent research shows that, in addition to their central role in the maize chemical defense repertoire, benzoxazinoids may have important functions in regulating other defense responses, flowering time, auxin metabolism, iron uptake and perhaps aluminum tolerance. Investigation of natural variation in maize benzoxazinoid accumulation, which is greatly facilitated by recent genomics advances, will have a major impact in this research area by leading to the discovery of previously unknown genes and functions of benzoxazinoid metabolism.